O TRABALHO NA ERA DIGITAL E OS DESAFIOS DA EMANCIPAÇÃO - Ricardo Colturato Festi (Universidade Federal do Maranhão, 2020)
This article seeks to contribute to the reflection about the challenges of the left in the face of the new technological revolution in progress, the so-called Fourth Industrial Revolution or Industry 4.0. To this end, he will briefly visit some authors who have faced technological revolutions in the past decades, particularly in the world of work, to show the various possibilities for positive and negative interpretations of these processes. Then, it will point out some questions about the ongoing revolution, in particular the transformations in work and social relations produced by “digital platforms”. Finally, without any intention of exhausting the debate, it will outline some issues that it considers challenges for the left and critical thinking in the face of these changes.